Pop-Up Festival as a Social Space for Strengthening Communities and Enhancing the Creative Capacity of Local Brands: A Qualitative Study in the Urban Area of Surabaya - Diffa Shalavy Putri; Santi Isnaini (Communicator Sphere, 2026)
Pop-up festivals have increasingly emerged as temporary urban interventions that activate public spaces and support the growth of local creative industries. However, existing studies have paid limited attention to how these festivals function as social spaces that strengthen community relations and enhance the creative capacity of local brands. This study aims to examine how participation in pop-up festivals contributes to community empowerment, social learning, and creative capacity development among local brands in Surabaya, Indonesia. This research employed a qualitative-exploratory approach involving three local brands: Rayu Manis, Kaluna Living, and LoveZane. Data were collected through semi-structured interviews, participatory observation, and documentation analysis during several pop-up festivals throughout 2025. The data were analyzed using thematic analysis following Braun and Clarke (2006). The findings reveal that pop-up festivals function not only as commercial platforms but also as creative incubation spaces that facilitate collaboration, identity expression, adaptive learning, and community networking. Public spaces become socially produced environments where emotional connection and creative experimentation occur simultaneously. This study concludes that inclusive and participatory festivals can strengthen local creative ecosystems. Therefore, policymakers and festival organizers are encouraged to design more accessible, collaborative, and value-driven public festival spaces to support sustainable creative development.